2021
DOI: 10.1136/oemed-2020-106914
|View full text |Cite
|
Sign up to set email alerts
|

Slip-resistant footwear reduces slips among National Health Service workers in England: a randomised controlled trial

Abstract: ObjectivesAssess the effectiveness of 5* GRIP-rated slip-resistant footwear in preventing slips in the workplace compared to usual footwear (control group).MethodsA multicentre, randomised controlled trial; 4553 National Health Service (NHS) staff were randomised 1:1 to the intervention group (provided with 5* GRIP-rated slip-resistant footwear) or the control group. The primary outcome of incidence rate of self-reported slips in the workplace over 14 weeks was analysed using a mixed-effects negative binomial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 6 publications
(11 reference statements)
0
4
0
Order By: Relevance
“…After exclusions due to withdrawals and missing data, 4504 (2257 intervention, 2247 control) participants were included in the analysis. The full participant flow diagram6 and descriptions of all baseline variables2 are reported elsewhere.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After exclusions due to withdrawals and missing data, 4504 (2257 intervention, 2247 control) participants were included in the analysis. The full participant flow diagram6 and descriptions of all baseline variables2 are reported elsewhere.…”
Section: Resultsmentioning
confidence: 99%
“…The strengths and limitations of the SSHeW trial are discussed in detail elsewhere 2 6. Briefly, the main strengths of a robust methodology, large sample size and high engagement, generated high-quality data that can be used in secondary analyses such as that presented here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thies [56] found that by increasing the degree of the forefoot rocker, minimum toe clearance in older adult participants also increased. Menant [18,20,21] also found negligible differences in footwear that included either a flared or bevelled heel block compared to the control and other active comparator conditions Further research is required to determine which modification to sole geometry is most effective Outsole tread Menant [18][19][20][21] found that shoes with an outsole tread were neither beneficial nor detrimental to balance performance compared to the control conditions, suggesting that shoes with an outsole tread may be worthy of consideration as they do not seem to impair balance performance Outsole tread did not impact balance, however it is likely to influence slipping in wet conditions [72][73][74] and should therefore be a consideration in older adults Minimalist footwear Cudejko [55] reported that older adults with a history of falls had better performance in the Timed Up and Go and star excursion balance tests when in minimalist shoes compared to conventional footwear and barefoot condition, while Petersen [67] found minimalist shoes to increase local dynamic stability and reduce minimum toe clearance variability in older adults. However, Menz [26] found minimalist shoes to have no effects on temporo-spatial parameters in older women when compared to the control and comparator conditions…”
Section: Sole Geometry or Rocker Solesmentioning
confidence: 99%